Seasonal influenza vaccination: from hesitancy to social norm - Malik, Asif Parvez; Sumathipala, Sanjeewa (International Journal of Research in Medical Sciences, 2021)
Seasonal influenza is of the most globally burdening vaccine-preventable diseases, infecting 3-5 billion people annually and according to the World Health Organisation (WHO) resulting in 250,000 to 500,000 deaths worldwide. Vaccination against influenza and all respiratory infections carries greater emphasis in the light of the COVID-19 pandemic. With added pressure on healthcare systems due to the coronavirus, Qatar is one country that is keen to emphasise the importance of influenza vaccination to prevent potential co-infection causing severe disease especially in high-risk groups. Currently seasonal influenza vaccines protect against 3 or 4 strains with revised data from the WHO twice yearly due to the changing natures of strains helping to maximise efficacy of the vaccines. It is recommended for specific high-risk groups to be prioritised for vaccination, including pregnant women, the elderly, children above 6 months of age, patients with chronic conditions as well as front line healthcare workers with risk of exposure. However, uptake of the vaccine remains low and contributes significantly to the burden of the disease. Barriers to vaccine uptake can be physical, such as unhealthy lifestyles, psychological, such as perception of disease as low-risk, contextual, such as lack of access to vaccinations, or sociodemographic, such as living alone. Vaccine coverage can be increased by knowledge of these barriers and how to address them. The physical barriers highlight the need to support behavioural change in lifestyle in order to increase vaccine uptake. Psychological barriers, usually due to misconceptions, can be addressed with education through public health campaigns and interactions between health professionals and patients. This education is not just a need for patients but also healthcare workers. It is up to healthcare providers and contractors to find ways of addressing contextual and sociodemographic barriers by increasing access to vaccination whether through transport, or home–care etc. A key barrier of those mentioned to vaccination is a lack of knowledge which needs to be addressed though positive discussions about the health benefits of immunisation as well as the traditional idea of disease-risk prevention. Addressing the above barriers will help to increase vaccine uptake, and produce health-conscientious societies where vaccination becomes a social norm.